The c-Myc/TBX3/nucleolin/Hsc70 signalling axis in breast cancer - Ncube, Stephanie Maria (Department of Human Biology, 2022)
The T-box transcription factor TBX3, plays critical roles in development including the formation of the limbs, heart and mammary glands. While haploinsufficiency of TBX3 results in ulnar mammary syndrome, its overexpression is linked to several cancers. We and others have shown that TBX3 drives tumour formation, invasion and metastasis of several sarcoma subtypes as well as melanoma, cervical cancer and breast cancer. TBX3 has thus been proposed as a novel therapeutic target to treat these cancers. Direct targeting of transcription factors for therapies however continues to represent a serious challenge and therefore an understanding of the molecular mechanisms that regulate and mediate its oncogenic activity may reveal more amenable anti-cancer drug targets. This project therefore aimed to (1) identify signalling molecules that upregulate TBX3 expression in MCF-7 breast cancer cells as well as (2) identify and characterize protein partners that cooperate with TBX3 to drive its oncogenic functions in these cells. The overexpression of the basic helix-loop-helix oncogenic transcription factor c-Myc has been widely reported in breast cancer progression and c-Myc-driven pathways are elevated in aggressive drug resistant breast cancer cells and tumours. Our laboratory has previously shown that c-Myc directly binds and activates the TBX3 promoter in several sarcoma subtypes, and it was hypothesised that c-Myc may also activate TBX3 in breast cancer. To investigate this, the impact of transiently knocking down c-Myc on TBX3 mRNA and protein levels was firstly assessed by qRT-PCR and western blotting respectively. Results show that when c-Myc is depleted, TBX3 mRNA and protein levels decrease, suggesting that c-Myc may be transcriptionally upregulating TBX3. To confirm this, c-Myc was ectopically overexpressed in MCF-7 breast cancer cells in the presence or absence of Actinomycin D, an inhibitor of de novo transcription, and TBX3 mRNA and protein levels were measured by qRT-PCR and western blotting respectively. Indeed, results show that when de novo transcription is inhibited, the c-Myc mediated activation of TBX3 expression is abolished. To identify and characterize TBX3 protein partners, MCF-7 breast cancer cells that stably overexpress FLAG-TBX3 were firstly established to enable effective immunoprecipitation for mass spectrometry. The overexpression of FLAG-TBX3 was confirmed by western blotting and immunocytochemistry and the anti-proliferative and pro-migratory roles of TBX3 overexpression in breast cancer cells was confirmed using growth curves and scratch motility assays respectively. Through affinity purifications coupled with mass spectrometry a myriad of putative TBX3 protein co-factors were identified and from this list three partners viz nucleolin, Hsc70 and HnRNP K were validated by immunoprecipitation and colocalization experiments. Importantly, results show that the interaction of TBX3 with Hsc70 is required for TBX3 protein stability and that nucleolin and TBX3 cooperate to promote MCF-7 breast cancer cell migration. Furthermore, treatment of MCF-7 cells with the nucleolin targeting aptamer, AS1411, mis localizes TBX3 and nucleolin to the cytoplasm and causes a reduction in cell viability while having no effect on the viability of normal skin fibroblasts. Together the results from this study show that c-Myc/TBX3/nucleolin/Hsc70 may be an important oncogenic pathway in breast cancer and that AS1411 may be a potentially important aptamer for the treatment of TBX3-driven breast cancer.